Short Communication Location of Seed-borne Inoculum of Lasiodiplodia theobromae and its Transmission in Seedlings of Pumpkin (Cucurbita pepo) (Biological Sciences - PJSIR, 2006)
Using naturally infected seeds of pumpkin, the fungus pathogen Lasiodiplodia theobromae (syn. Botryodiplodia theobromae) was located on and in the seed coat, including tegmen, and in the tissues of the cotyledons and embryo. Apparently healthy seeds showed incidence of the fungus in seed coat and tegmen. The fungus was transmitted to seedlings and caused pre- and post-emergence damping-off desease, resulting in increase in the inoculum potential of L. theobromae in the agricultural fields.